Ventilator hyperinflation determined by peak airway pressure delivered: A randomized crossover trial. Issue 1 (19th January 2020) - Jacob, Wendy; Dennis, Diane; Jacques, Angela; Marsh, Lisa; Woods, Paul; Hebden‐Todd, Tracy
Abstract: Aim: The aim of this study was to see if a more sophisticated ventilator hyperinflation protocol might result in more sputum clearance compared to manual hyperinflation. Background: Hyperinflation has been used to mobilize lung secretions in mechanically ventilated patients in the intensive care unit setting for almost 50 years. In the past decade, rather than using a bag external to the ventilator circuit to deliver hyperinflation (known as "bagging" or "manual hyperinflation"), a new technique has evolved using existing ventilator circuitry (known as "ventilator hyperinflation"). One conservative ventilator hyperinflation protocol has demonstrated equivalence with manual hyperinflation in sputum clearance. Design: A randomized crossover study. Method: Patients received manual hyperinflation and ventilator hyperinflation in two randomly ordered treatments on the same day by the same physiotherapist, using a ventilator hyperinflation protocol involving titration of hyperinflation according to airway pressure. Results: Between 2013 and 2018, 48 patients were enrolled in the study. Physiotherapy treatment using ventilator hyperinflation yielded significantly more wet weight sputum (median 2.84 g, IQR 1.81, 4.22) than treatment using manual hyperinflation (median 1.5 g, IQR 0.73, 2.31, P  < .001), without significant differences in secondary measures. Conclusions: A more sophisticated approach to the titration of the volume delivered using ventilator hyperinflation relative to the airway pressure resulted in greater wet weight sputum cleared during physiotherapy treatment. Relevance to Clinical Practice: The results presented in this paper demonstrate that the application of ventilator hyperinflation using peak airway pressure rather than tidal volume may be superior in facilitating sputum clearance and improved oxygenation without patient harm.